Correction to: low coverage sequencing for repetitive DNA analysis in Passiflora edulis Sims: citogenomic characterization of transposable elements and satellite DNA - Vanessa Carvalho Cayres Pamponét; Margarete Magalhães Souza; Gonçalo Santos Silva; Fabienne Micheli; Cláusio Antônio Ferreira de Melo; Sarah Gomes de Oliveira; Eduardo Almeida Costa; Ronan Xavier Corrêa (BMC Genomics, 2019)
.